In-silico core proteome analysis for chimeric vaccine development against tick-borne tularemia - Bader S. Alotaibi; Fatiha Khan; Muhammad Bilal Iqbal Rehmani; Fizza Arshad; Muhammad Umer Khan; Umar Nishan; Abid Ali; Khaled Fahmi Fawy; Sarah A. Altwaim; Saeed M. N. Alasmari; Hanna Dib; Mohibullah Shah (PLoS ONE, 2025)
Tularemia is an extremely contagious zoonotic illness resulting from infection with the intracellular bacterium Francisella tularensis . It is transmitted primarily via vector bites particularly from ticks, flies, and mosquitoes and is a severe public health threat. Because of its high virulence, low infective dose, aerosol transmissibility, and potential for mass casualties, F. tularensis is also considered a potential biological warfare agent. Despite its severity, there is presently no licensed vaccine against this pathogen. In the present work, a subtractive proteomics pipeline was implemented to identify potential antigenic targets to prepare a multi-epitope vaccine. Five vaccine constructs were generated through the combination of B-cell, HTL, and CTL epitopes with suitable adjuvants and linkers. Among these, two constructs V1 and V2 were extremely non-allergenic and antigenic. To assess immune receptor engagement, molecular docking was conducted with TLR4 and TLR5, followed by 200 ns molecular dynamics simulations. Vaccine-receptor complexes were analyzed using RMSD, RMSF, radius of gyration (Rg), Dynamic Cross-Correlation Matrix (DCCM), SASA, PCA, H-bond analysis and MMPBSA binding energy calculations, all confirming structural stability and strong binding affinity. In-silico cloning revealed a GC content of 50% and 1.0 codon adaptation index (CAI), suggesting high expression potential in E. coli . Immune simulation further supported the construct`s ability to elicit a robust and long-lasting immunity. These computational findings highlight the potential of the constructed vaccines as effective candidates against F. tularensis , though experimental substantiation is requisite.